Effects of increasing L-lysine HCl in corn-soybean meal diets on growth performance and carcass characteristics of growing-finishing gilts - De La Llata, M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An experiment using 1,200 gilts (65 to 260 lb) was conducted to determine the effects of increasing L-lysine HCl in cornsoybean meal diets on growth performance and carcass characteristics. The dietary treatments consisted of a control diet with no added L-lysine HCl and six increasing levels of L-lysine HCl (1, 2, 3, 4, 5, and 6 lb/ton) replacing the lysine provided by soybean meal. A negative control treatment was used to ensure that dietary lysine was not above required levels. Increasing L-lysine HCl above 3 lb/ton decreased ADG and increased F/G. Backfat was increased and FFLI decreased with increasing L-lysine HCl in the diet, and the greatest responses occurred at levels above 3 lb/ton. These results indicate that no more than 3 lb/ton (.15%) of L-lysine HCl should be added to corn-soybean meal diets for growing-finishing pigs unless other synthetic amino acids are added to avoid deficiencies that compromise growth performance.
Keywords: Swine; Lysine; Corn; Finishing Pigs